The Effectiveness of Distance Learning from the Perspective of Graduate Students of the Faculty of Educational Sciences at Mutah University in Light of Corona Crisis - Mohammad Ahmad Bani Amer (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study explores the graduate students of the faculty of educational science's perceptions towards distance learning during the corona crisis at Mutah University. The study involved 125 graduate students attending Doctorate, Master, and High Diploma programs in Educational Sciences at Mutah University in the second semester of academic year 2020\2021. Data had collected among graduate students of the faculty of educational sciences of Mutah University, Al-Karak, Jordan, through an online questionnaire. The study followed a quantitative approach, where the survey technique was used as an instrument of data collection. Results showed that most graduate students of the faculty of educational sciences were satisfied with the effectiveness of distance learning at Mutah University in light of the Corona crisis. Thus, they didn't face challenges in distance learning, and the majorities of the students preferred distance learning to conventional types and understand the content of virtual classes easily. Besides, the study discovered that Master's students showed a better view than Doctorate and High Diploma students regarding distance learning, and female students have more positive appreciation than male students.